Sensory Attributes of Pork Pickle Incorporated with Fermented Bamboo Shoot - Chavhan, D.M.; Hazarika, M.; Brahma, M.L.; Rahman, Z. (Journal of Meat Science, 2014)
This study was conducted to evaluate the organoleptic quality of pork pickles prepared by replacing vinegar with fermented bamboo shoot (FBS) at different levels (50% and 100% replacement). Organoleptic evaluation of the products revealed that all the products were equally acceptable as no significant differences were observed, however, pork pickle with FBS powder and extract were preferred more compared to FBS extract. The costs of FBS incorporated pickle products were found to be lower than the control product. Based on the above study, it can be concluded that FBS products can be used to replace the conventional chemical preservative in pork pickle which are cheaper, organoleptically tastier and highly acceptable. There is high prospect of using these natural indigenous products commercially in manufacturing pork pickle in India.